2020
DOI: 10.17652/rpot/2020.3.19713
|View full text |Cite
|
Sign up to set email alerts
|

Modelos de Gestão por Competências: Um estudo longitudinal em uma empresa automobilística

Abstract: Os Modelos de Gestão por Competência (MGC) são concebidos para alinhar as práticas de gestão de pessoas entre si, integrados à estratégia organizacional. Entretanto, tais modelos podem diferir significativamente entre si, conforme incorporam ou não elementos estratégicos, como as competências organizacionais. O respectivo estudo de caso analisou tais questões na implantação e revisões subsequentes de um MGC em uma multinacional do setor automobilístico. A metodologia investigativa utilizou estudo qualitativo, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Como a gestão do conhecimento dedica atenção especial ao estudo da dimensão cognitiva, pode-se dizer que ela promove o desenvolvimento de competências. (KNAPIK et al, 2020). A competência, uma vez desenvolvida, faz nascer novas necessidades, incentivando a criação de novos conhecimento.…”
Section: Desenvolvimentounclassified
“…Como a gestão do conhecimento dedica atenção especial ao estudo da dimensão cognitiva, pode-se dizer que ela promove o desenvolvimento de competências. (KNAPIK et al, 2020). A competência, uma vez desenvolvida, faz nascer novas necessidades, incentivando a criação de novos conhecimento.…”
Section: Desenvolvimentounclassified
“…In his paper, Otoo (2020) examined the mediating role of employee competencies in the association between HRM practices and the organizational effectiveness of the pharmaceutical industry. Knapik, Fernandes, and Sales (2020) analyzed such issues in the implantation and subsequent revisions of a competency management model in their work. In his article, Zupančič (2020) highlighted the importance of investments in competencies.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Organizations incorporate competencies as a management tool in the CBM model which, according to Redmond (2013, p. 771), "is a written and often graphically enhanced description of the desired competencies that are derived from the firm's strategy and are intended to facilitate organizational growth and change". CBM models are used to align people management practices (recruitment and selection, assessment, training and development, career, compensation, talent management) and relate them to strategy (Knapik, Fernandes, Sales, 2020;Sani et al, 2016;Audenaert, Vanderstraeten, Buyens, & Desmidt, 2014;Redmond, 2013). Considering that organizational competencies require unique resources to make strategies feasible, it is plausible to assume that the individual competencies elected for the composition of a CBM model reflect the uniqueness of the organization's strategies and competences (Salman, Ganie, & Saleem, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Career axes and work levels concepts are characteristic of modern CBM models (Knapik et al, 2020;Campion et al, 2011), insofar as that implies describing competencies in a differentiated manner, according to a professional's position, in contrast to traditional models that propose the same competencies for everyone, regardless of work process and career level. For example, Knapik et al (2020), when carrying out a longitudinal study in an automotive company that adopted several CBM models over time, with different conceptual bases, found that the model that prevailed and was adopted at the end of the period-due to its functionality -,, incorporated concepts of career axes, work levels and competencies as deliveries.…”
Section: Theoretical Frameworkmentioning
confidence: 99%